Model of Strategy to Increase Patient Interest in Visiting Hospitals after the Covid-19 Pandemic - Niluh Desy Purnamasari; Subardin AB Subardin AB; Sudirman Sudirman (GLOBAL HEALTH SCIENCE GROUP, 2024)
The COVID-19 pandemic has caused a significant decrease in hospital visits due to fear of virus transmission. RSUD Anuntaloko Parigi, experienced a decrease in patient visits after the pandemic, requiring strategies to increase patient interest. This study explores the TOWS matrix, which evaluates internal factors (strengths and weaknesses) and external factors (opportunities and threats). Objective: This study aims to find strategies increase patient visit interest in the Regional General Hospital (RSUD) after the Covid-19 pandemic period. Method: A quantitative descriptive study with a cross-sectional design was conducted involving 12 respondents through structured interviews. Data were analyzed usinga TOWS analysis framework was applied in excel program and Descriptive analytics. Results: Results indicated that external opportunities outweighed threats, scoring 5.51, while internal strengths surpassed weaknesses, scoring 11.64. The hospital is positioned in the progressive quadrant, suggesting it can leverage its strengths to seize opportunities. Key strategies identified include improving comfort, and cleanliness, collaboration with BPJS, and program knowledge, patient education and utilizing social media for digital engagement. Conclusions: Anuntaloko Parigi Hospital has great opportunities, in a progressive position. Relevant strategies are improving comfort, cleanliness, and cooperation with BPJS, as well as program introduction, patient education, and utilization of social media in promotion.